Diversification of Device Platforms by Molecular Layers: Hybrid Sensing Platforms, Monolayer Doping, and Modeling - Yitzchaik, Shlomo; Gutierrez, Rafael; Cuniberti, Gianaurelio (Giovanni); Yerushalmi, Roie (Langmuir, 2018)
Inorganic materials such as semiconductors, oxides, and metals are ubiquitous in a wide range of device technologies owing to the outstanding robustness and mature processing technologies available for such materials. However, while the important contribution of inorganic materials to the advancement of device technologies has been well established for decades, organic-inorganic hybrid device systems, which merge molecular functionalities with inorganic platforms, represent a newer domain that is rapidly evolving at an increasing pace. Such devices benefit from the great versatility and flexibility of the organic building blocks merged with the robustness of the inorganic platforms. Given the overwhelming wealth of literature covering various approaches for modifying and using inorganic devices, this feature article selectively highlights some of the advances made in the context of the diversification of devices by surface chemistry. Particular attention is given to oxide-semiconductor systems and metallic surfaces modified with organic monolayers. The inorganic device components, such as semiconductors, metals, and oxides, are modified by organic monolayers, which may serve as either active, static, or sacrificial components. We portray research directions within the broader field of organic-inorganic hybrid device systems that can be viewed as specific examples of the potential of such hybrid device systems given their comprehensive capabilities of design and diversification. Monolayer doping techniques where sacrificial organic monolayers are introduced into semiconducting elements are reviewed as a specific case, together with associated requirements for nanosystems, devices, and sensors for controlling doping levels and doping profiles on the nanometric scale. Another series of examples of the flexibility provided by the marriage of organic functional monolayers and inorganic device components are represented by a new class of biosensors, where the organic layer functionality is exploited in a functioning device for sensing. Considerations for relying on oxide-terminated semiconductors rather than the pristine semiconductor material as a platform both for processing and sensing are discussed. Finally, we cover aspects related to the use of various theoretical and computational approaches to model organic-inorganic systems. The main objectives of the topics covered here are (i) to present the advances made in each respective domain and (ii) to provide a comprehensive view of the potential uses of organic monolayers and self-assembly processes in the rapidly evolving field of molecular-inorganic hybrid device platforms and processing methodologies. The directions highlighted here provide a perspective on a future, not yet fully realized, integrated approach where organic monolayers are combined with inorganic platforms in order to obtain versatile, robust, and flexible systems with enhanced capabilities.
CRIS-Team Scopus Importer:2022-04-14